Impact of Facebook Toward Social Collective Action Among Malaysia Youth During Movement Control Order Case Studies With Caremongering Malaysia - Mansuri Abadi; Putu Ayu Suniadewi (Austronesia Akademika, 2025)
The enforcement of Malaysia’s Movement Control Order (MCO) 1.0 during the first wave of COVID-19 created widespread panic, social disconnection, and practical hardships, especially for vulnerable groups, while also intensifying the need for rapid, community-based responses. Within this context, Facebook emerged as a new public sphere that enabled young people to organize collective action through the Caremongering Malaysia movement. This study aims to examine the reasons behind the movement’s formation, identify the strategies it employed, and explain how it sustained mobilization during and beyond MCO 1.0. Using a qualitative approach grounded in a constructivist paradigm, the research collected primary data through group discussions, in-depth interviews, and participatory observation involving eight coordinators and volunteers, supported by secondary literature. The findings show that Caremongering Malaysia was driven by a combination of collective identity, disappointment with government responses, and social solidarity. Its mobilization was sustained through three core principles mutual aid, direct action, and autonomy which were operationalized through decentralized coordination, need-based assistance, digital networking, interactive mapping, and inclusive volunteerism across diverse social backgrounds. The movement also helped connect aid seekers and volunteers efficiently nationwide. The study concludes that Facebook functioned not merely as a communication platform but as an effective infrastructure for grassroots mobilization, enabling Malaysian youth to strengthen solidarity.